The Secret Lives of Church Ladies - Philyaw, Deesha (Book collections on Project MUSE., 2020)
"The Secret Lives of Church Ladies explores the raw and tender places where black women and girls dare to follow their desires and pursue a momentary reprieve from being good. The nine stories in this collection feature four generations of characters grappling with who they want to be in the world, caught as they are between the church's double standards and their own needs and passions"--